“NARRATIVE OF THE SELF “: THE DISCOURSE OF DAILY LIFE IN THE ESSAYS BY PARTICIPANTS OF LITERACY WORKSHOP - Rahayu, Mundi; Rakhmawati, Deny Efita Nur (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2020)
Literacy workshop is important activity delivered in community to increase people’s competencies not only in reading and writing, but more importantly in building critical perspectives. However, the result of the literacy workshop needs to be examined, not only to find out the success indicator of the workshop, but also to understand the narration presented in young peoples‘ works. It is necessary to get the idea of what the young people’s concern and thought. This paper discusses the writings as the products of literacy workshop held at Trenggalek, East Java, which was attended by young people as participants. The workshop results in 12 writings, consisting of two short stories, and 10 essays. The questions raised in this paper are; how is the discourse of daily life represented in the writings of the literacy workshop participants? What are the social and cultural factors affecting the writers in constructing the discourse? This paper argues that young people’s concern reflects the current social cultural issues that matters in our life. Literacy for young people is not merely giving the skill of reading and writing, but it is a meaning-making process, that enable them to construct the meaning of their everyday life.